Persistent pain after cesarean delivery. (November 2019) - Sun, K.W.; Pan, P.H.
Highlights: Prevalence of persistent pain after cesarean delivery varies. The prevalence is lower than comparable surgery. Peripartum state and oxytocin may play a role in preventing persistent pain. The risk is associated with severity of acute pain and opioid exposure. Surgical techniques, neuraxial anesthesia and opioid-sparing may be preventative. Abstract: The incidence of persistent pain after cesarean deliveries (CD) varies but is much lower than after comparable surgeries. However, with over four million deliveries annually and a rising CD rate, even a low prevalence of persistent pain after CD impacts many otherwise healthy young women. Consideration of the pathophysiology of persistent pain after surgery and the risk factors predisposing women to persistent and chronic pain after CD provides insights into the prevention and treatment of persistent pain; and improves the quality of care and recovery after CD. The findings that the peripartum state and oxytocin confer protection against persistent pain may provide new and interesting perspectives for the prevention and treatment of chronic pain caused by trauma or surgery. Predictive tools available to identify and target patients at high risk of acute and chronic pain have mostly weak to modest predictive correlations and many are either not clinically feasible or too time-consuming to apply. Persistent pain has been linked to the severity of acute postoperative pain and opioid exposure. Modified surgical techniques, neuraxial anesthesia and opioid-sparing analgesia may help limit the development of persistent and chronic pain. The goal of this narrative review is to examine the incidence of persistent pain after CD; review briefly the underlying pathophysiology of persistent pain and the transition from acute to chronic pain (with particular emphasis on the uniqueness after CD); and to review modifiable risk factors and prevention strategies that identify at-risk patients and allow tailored treatment.